Pengaruh Job Satisfaction, Conflict Management, Leadership Style Terhadap Employee Commitment Pada PT Bina Media Tenggara - Rehan putra dharmawan; Netania Emilisa; Charles Mercelie (Journal of Economics and Business UBS, 2023)
This study aims to analyze the effect of Job Satisfaction, Conflict Management, Leadership Style on Employee Commitment. This research was conducted using quantitative approach and survey method by taking samples from employees at Bina Media Tenggara company. The data were analyzed using multiple regression analysis techniques. A total of 225 samples were collected. The results showed that Job Satisfaction, Conflict Management and Leadership Style significantly affect Employee Commitment. This finding shows that employees with high Job Satisfaction, positive Conflict Management roles, and good Leadership Style can increase Employee Commitment in the company. This research provides practical implications for companies in increasing Employee Commitment. It is very important for companies to pay attention to these factors, because it can increase Job Satisfaction which affects Employee Commitment to achieve company goals.